How do you solve x^2-3x-12=0?

1 Answer
Apr 24, 2017

x~~5.275
x~~-2.275

Explanation:

There are many ways to solve a quadratic equation.
Look here if you are lost on how to solve quadratic equations.

When in doubt you can't go wrong with using the quadratic formula.

x=(-b+-sqrt(b^2-4ac))/(2a)

where ax^2+bx+c=0


For x^2-3x-12=0

a=1
b=-3
c=-12

Now just substitute into the quadratic formula

x=(-(-3)+-sqrt((-3)^2-4(1)(-12)))/(2(1))

x=(3+-sqrt(9+48))/(2)

x=(3+-sqrt(57))/(2)

Therefore,

x=(3+sqrt(57))/(2) ---> ~~5.275

OR

x=(3-sqrt(57))/(2) ---> ~~-2.275